Outcomes of Concomitant Fractures of the Radial Head and Capitellum: The “Kissing Lesion” - Claessen, F M. A. P.; Kachooei, A R.; Verheij, K K. J.; Kolovich, G P.; Mudgal, Chaitanya S. (Journal of Hand and Microsurgery, 2016)
Background Radial head compression against the capitellum may cause concomitant fracture of the capitellum. The purpose of this study was to investigate if radial head fracture type is associated with a concomitant fracture of the capitellum.Patients and Methods Data were identified from five area hospitals. We retrieved records of patients older than 18 years of age who underwent treatment for concomitant capitellum fracture and radial head fracture between January 2002 and January 2013. Patients with olecranon fractures or trochlea fractures were excluded.Results A total of 10 patients with a radial head fracture and a concomitant capitellum fracture were included. Based on the operative reports, nine radial head fractures were classified as Hotchkiss modification of the Mason classification type II, and one was classified as type I. Based on the available radiographs and computed tomography, three capitellum fractures were type I, and seven were type II according to the Grantham classification.Conclusion Surgeons have to be alert to capitellar damage in case of a Hotchkiss type II radial head fracture.Level of Evidence This is a level IV, therapeutic, retrospective study.
Keywords: radial head; capitellum; concomitant; fracture